RPA-1 from Leishmania amazonensis (LaRPA-1) structurally differs from other eukaryote RPA-1 and interacts with telomeric DNA via its N-terminal OB-fold domain - Pavani, R. S. [UNESP]; Fernandes, C. [UNESP]; Perez, A. M.; Vasconcelos, E. J. R.; Siqueira-Neto, J. L.; Fontes, M. R. [UNESP]; Cano, M. I. N. [UNESP] (Elsevier B.V., 2014)
Replication protein A-1 (RPA-1) is a single-stranded DNA-binding protein involved in DNA metabolism. We previously demonstrated the interaction between LaRPA-1 and telomeric DNA. Here, we expressed and purified truncated mutants of LaRPA-1 and used circular dichroism measurements and molecular dynamics simulations to demonstrate that the tertiary structure of LaRPA-1 differs from human and yeast RPA-1. LaRPA-1 interacts with telomeric ssDNA via its N-terminal OB-fold domain, whereas RPA from higher eukaryotes show different binding modes to ssDNA. Our results show that LaRPA-1 is evolutionary distinct from other RPA-1 proteins and can potentially be used for targeting trypanosomatid telomeres. (C) 2014 Federation of European Biochemical Societies. Published by Elsevier B.V. All rights reserved.
Keywords: LaRPA-1; Leishmania amazonensis; Telomeres; OB-fold domain; Replication protein A subunit 70 kDa; Replication factor 1